Lifestyle and Age-Related Determinants of Male Fertility: Evidence from Semen Analysis in Western Libya - Ghadda Mohamed,; Naamat Abid, (AlQalam Journal of Medical and Applied Sciences, 2025)
Male fertility is influenced by a range of lifestyle and age-related factors. This study aims to explore the impact of age and smoking status on semen quality parameters, contributing to public health awareness and targeted fertility interventions. A retrospective analysis was conducted on medical records of 159 male patients aged 25–65 years, sourced from laboratories including the Sabratha Hospital Sanitarium. Semen parameters assessed included volume, abstinence duration, pH, sperm count, progressive motility, morphological abnormalities, and aggregation. Data were analyzed using SPSS 25 and Excel 2010, applying descriptive statistics, t-tests, and Pearson correlation coefficients. Statistical significance was set at P < 0.05 and P < 0.001. The majority of participants were aged 35–45 years (42.8%) and non-smokers (62.9%). Most semen parameters fell within normal WHO reference ranges, with 74.8% showing normal sperm counts and 99.4% exhibiting normal progressive motility. T-test analysis revealed a statistically significant reduction in sperm count among smokers (P = 0.003), while no significant differences were found in sample volume, abnormalities, or motility. Pearson correlation indicated strong negative associations between sperm count and smoking, and moderate negative correlations for sample volume and motility. Other variables showed weak or non-significant correlations. Smoking is significantly associated with reduced sperm count, while other semen parameters appear unaffected. Age distribution and abstinence duration also show variable influence. These findings underscore the need for lifestyle-focused fertility education and further research into modifiable risk factors affecting male reproductive health.